Chatting with Centralians : a recorded history of thirty Centralians - Brown, Shirley; Historical Society of the Northern Territory (Casuarina : Historical Society of the Northern Territory, 1998)
Interviewees include: Peg Nelson and Jean Hayes, Mabel Adamson, Gertie Turner, Minna Sitzler, Len Kittle, Alf Smith, Ted Smith, Evie Connellan, Anne and Damian Miller, Doff Gill, Marjory Kinane, Jane Maskell, Bob and Vicki Darken, Bill Waudby, Joan Higgins, Sister Eileen Heath, Reg Harris, Molly Clark, Sheila Hewitt, Pat Elvins, Nan Parker, Keith Castle, John Egar, Berna Madill, Keith Locke, Ian Jamieson and Stuart Traynor.
"The lives of 30 Centralians and their contributions to the growth of the Northern Territory"--cover.
Keywords: Frontier and pioneer life -- Australia, Central; Frontier and pioneer life -- Northern Territory -- Alice Springs Region; Australia, Central -- History; Alice Springs (N.T.) -- History